High-efficiency rectifier achieves 63% power conversion in low start-up voltage for UHF RFID tags in 180 nm CMOS technology - Zahra Sahel; Sanae Habibi; Abdelhak Bendali; Abid Reda El Wardi; Karima Benkhadda; Samia Zarrik; Hayat El Abassi; Fatehi ALtalqi; Omar Mouhib; Mohamed Habibi (Universitas Ahmad Dahlan, 2024)
This paper presents an N-metal-oxide semiconductor (NMOS) rectifier designed for efficient radio frequency (RF) energy harvesting and wireless power transmission in passive ultra-high frequency (UHF) radio frequency identification (RFID) applications. The rectifier’s efficiency is improved through an innovative diode with a new block connection, reducing the threshold voltage compared to conventional diode transistors. This enhancement significantly boosts output voltage and efficiency. A seven-stage configuration, based on the proposed diode and optimized via a superposition method, has been evaluated for its ability to increase DC output voltage and power conversion efficiency (PCE), particularly at low RF input power levels. Simulations show a PCE of 63% at 900 MHz with an RF input of -11 dBm, delivering 1.610 V across a 0.518 MΩ load. Notably, the rectifier maintains a PCE above 30% across a wide input power range from -32 dBm to -5 dBm, overcoming a key challenge of maintaining efficiency under low input power conditions. The circuit architecture was implemented using standard 180 nm TSMC CMOS technology, showcasing its practical applicability in RFID systems.